Corporate finance and the securities laws - Johnson, Charles J. (Aspen Law &​ Business, 1997)
Corporate Finance and the Securities Laws, the best-selling classic on investment banking and securities regulation, is now available in an expanded and completely updated second edition by Charles J. Johnson, Jr., the original author, and Joseph McLaughlin, a partner at Brown &​ Wood LLP and former General Counsel at Goldman, Sachs &​ Co.